2020
DOI: 10.2147/dmso.s240122
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effects of 24-Week, High-Concentration Hydrogen-Rich Water on Body Composition, Blood Lipid Profiles and Inflammation Biomarkers in Men and Women with Metabolic Syndrome: A Randomized Controlled Trial</p>

Abstract: Purpose: Metabolic syndrome is associated with several medical risk factors including dyslipidemia, hyperglycemia, and obesity, which has become a worldwide pandemic. The sequelae of this condition increase the risk of cardiovascular and neurological disease and increased mortality. Its pathophysiology is associated with redox dysregulation, excessive inflammation, and perturbation of cellular homeostasis. Molecular hydrogen (H 2) may attenuate oxidative stress, improve cellular function, and reduce chronic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
66
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 37 publications
4
66
2
2
Order By: Relevance
“…AEW is also used as a therapeutic substance, and was reported to reduce insulin resistance (IR) in animal models [ 19 , 20 ]. However, few studies have explored the antidiabetic effects of AEW in humans [ 21 , 22 , 23 , 24 , 25 , 26 ]. AEW was revealed to ameliorate blood glucose, MDA, interleukin-6 and tumor necrosis factor alpha [ 25 ], and to increase the oxidant potential [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AEW is also used as a therapeutic substance, and was reported to reduce insulin resistance (IR) in animal models [ 19 , 20 ]. However, few studies have explored the antidiabetic effects of AEW in humans [ 21 , 22 , 23 , 24 , 25 , 26 ]. AEW was revealed to ameliorate blood glucose, MDA, interleukin-6 and tumor necrosis factor alpha [ 25 ], and to increase the oxidant potential [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have explored the antidiabetic effects of AEW in humans [ 21 , 22 , 23 , 24 , 25 , 26 ]. AEW was revealed to ameliorate blood glucose, MDA, interleukin-6 and tumor necrosis factor alpha [ 25 ], and to increase the oxidant potential [ 26 ]. A study by Gadek et al [ 27 ] showed that patients who drank at least 2 L/day of AEW had significantly decreased blood glucose and glycated hemoglobin levels after treatment for 6 days.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in a human study, a hydrogen-rich water bath once daily for 6 months was reported to decrease visceral fat with reductions in low-density lipoprotein and fasting blood glucose levels [ 11 ]. Clinically, MH intake was reported to be effective against metabolic syndrome (MetS) [ 12 ] and the adverse effects of chemotherapy [ 13 ] and radiotherapy [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular hydrogen is currently recognized as an emerging therapeutic, as its supplemental application exerts protective effects in cardiovascular diseases [ 1 , 2 ], neurodegenerative diseases [ 3 ], inflammatory diseases [ 4 ], neuromuscular disorders [ 5 ], metabolic syndrome [ 6 ] diabetes [ 7 , 8 ], kidney disorders [ 9 , 10 ], and cancer [ 11 ]. The protective effects of molecular hydrogen are largely related to its antiapoptotic, anti-inflammatory, and antioxidative actions ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…They found that inhalation of 1.3% H 2 during PCI resulted in left ventricular (LV) reverse remodeling at six months after STEMI. The positive effects of H 2 were also demonstrated in metabolic syndrome ( n = 60) using a double-blinded, placebo-controlled trial [ 6 ]. The consumption of H 2 -rich water for 24 weeks led to a significant reduction in blood cholesterol, glucose levels, attenuated serum hemoglobin A1c, and improved biomarkers of inflammation and redox homeostasis as compared to the placebo group.…”
Section: Introductionmentioning
confidence: 99%